Linking Short-Chain Fatty Acids to Systemic Homeostasis: Mechanisms, Therapeutic Potential, and Future Directions - Yueru Zhao; Jing Chen; Yunlong Qin; Jinguo Yuan; Zixian Yu; Rui Ma; Fude Liu; Jin Zhao (Journal of Nutrition and Metabolism)
Short-chain fatty acids (SCFAs), pivotal metabolites derived from microbial fermentation of dietary fiber, serve as critical modulators of glucose and lipid metabolism. Dysregulation of SCFA levels, often stemming from inadequate fiber intake or dysbiosis of SCFA-producing microbiota, correlates with heightened susceptibility to diverse pathologies, including autoimmune disorders, metabolic syndromes, and malignancies. Emerging evidence underscores the pleiotropic roles of SCFAs in orchestrating gut and systemic homeostasis, positioning them as novel therapeutic candidates for immune dysregulation, inflammatory conditions, and transplant rejection. This review synthesizes current knowledge on SCFA biosynthesis, absorption dynamics, and their multifaceted regulatory mechanisms, spanning epigenetic modulation, G protein–coupled receptor (GPR) signaling, and immune cell crosstalk. We further elucidate their therapeutic potential in clinical contexts, emphasizing their capacity to recalibrate immune responses, suppress chronic inflammation, and mitigate oncogenesis. By integrating recent advances in microbiome research and translational applications, this work highlights the imperative for precision interventions targeting SCFA pathways to bridge the gap between microbial ecology and clinical innovation.